Re-Voting And Re-Vote Counting: Differences, Causes And Impact Factors - Rahmawati, Nurlaili (Jurusan Hukum Tatanegara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin, 2022)
This article examines the phenomenon of re-voting and recounting of ballots. Re-voting and recounting ballots is likened to an unpredictable stage of the electoral process because on particular districts, besides that with the devotees not all doing this. Re-voting and recounting ballots will add or even repeat either part or possibly all of the work that has been done by the Electoral Commission. Re-voting and recounting ballots could be due to constitutional court rulings, recommendation of bawaslu, and the state of force majeure. This will have an impact on budget addition, logistical willingness, voter attendance, longer conflicts and the integrity and professionalism of the Electoral Commission at stake. If the re-vote and the recount of the ballots are included in the stages of the election process and determined the date will result if the Constitutional Court decides outside the schedule of the process stages then it is feared that the date is not in accordance with the stages, Meanwhile, if the re-vote and recount of ballots do not become mandatory stages in the election, it is feared that with the simultaneous elections in 2024 the impact that occurs cannot be anticipated properly by the Election Commission. Keywords: Revote of ellection, recount of ballots, simultaneous elections 2024.